2004
DOI: 10.1136/ard.2003.012088
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of four shoulder-specific questionnaires in primary care

Abstract: Objectives: To compare the validity, responsiveness to change, and user friendliness of four self completed, shoulder-specific questionnaires in primary care. Methods: A cross sectional assessment of validity and a longitudinal assessment of responsiveness to change of four shoulder questionnaires was carried out: the Dutch Shoulder Disability Questionnaire (SDQ-NL); the United Kingdom Shoulder Disability Questionnaire (SDQ-UK); and two American instruments, the Shoulder Pain and Disability Index (SPADI) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
153
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 24 publications
6
153
3
4
Order By: Relevance
“…This exceeds MCID for SPADI, which is 8 points reduction (8). Eighteen patients (85.71%) would recommend dextrose Prolotherapy to other patients with a similar condition ( Figure 1) and no one patient reported significant side effects, which were not resolved within one week.…”
Section: Resultsmentioning
confidence: 99%
“…This exceeds MCID for SPADI, which is 8 points reduction (8). Eighteen patients (85.71%) would recommend dextrose Prolotherapy to other patients with a similar condition ( Figure 1) and no one patient reported significant side effects, which were not resolved within one week.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the "arm, shoulder, and hand" questionnaire has been used in some studies conducted on the patients with thoracic outlet syndrome [20][21][22]. In Table 1, the characteristics of the resources and in Table 2, two characteristics on evaluating the treatment outcomes [23][24][25][26] are presented.…”
Section: Resultsmentioning
confidence: 99%
“…These instruments are recommended for patients with thoracic outlet syndrome, however none of them has been validated and reliable in these patients and using them requires more research on their psychometric properties in these patients. Although, the studies showed that the psychometric properties of these instruments are acceptable for clinical use [23,25,34], the clinical use of them requires more research and examinations. For instance, the shortness of questionnaire, simple answering with yes/no, and very simple grading in "simple shoulder test" makes this questionnaire an attractive research clinical instrument but in the systematic-review studies, the least detectable change (MDC) and the least minimal clinically important difference (MCID) are not defined [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the correlation between some of the included scales was at best moderate. [54][55][56] Because of the large number of different range of movement measures used, following discussion with the advisory group these were prioritised for the analyses. The passive range of movement outcomes of interest were passive external rotation, passive internal rotation and passive abduction; and the active range of movement outcomes were active external rotation, active internal rotation and active abduction.…”
Section: Narrative Synthesis and Pair-wise Comparisonsmentioning
confidence: 99%